(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
An approach for the computation of the heat flux, which is needed for warming up of flat wood details during unilateral heating aimed at their plasticizing in the production of curved outside parts for corpses of stringed music instruments, has been suggested. The approach is based on the numerical integration and differentiation of the solutions of a linear model for the calculation of the non-stationary 1D temperature distribution along the thickness of subjected to unilateral heating flat wood details. The paper presents solutions of the model concerning the non-stationary change in the specific heat flux needed for warming up of flat spruce details with thicknesses of 6, 8 and 10 mm during their unilateral heating at temperatures of the electrically heated metal band equal to 100, 120, and 140 oC.